A prospective partial bio-based diamine-adenine-monomer platform for high performance polymer: A case study on phthalonitrile resin. (September 2019) - Liu, Yao; Hu, Jianghuai; Li, Renke; Li, Chengfeng; Liang, Bo; Liu, Yang; Peng, Weifeng; Zeng, Ke; Yang, Gang
Abstract: A novel partial bio-based molecular design platform for high performance polymer (HPP) namely diamine-adenine-monomer platform (DAAMP) was suggested and discussed in this paper. Aimed at introducing the adenine moiety into backbone of HPP and endowing great wide molecular tailorability, DAAMP was synthesized via a nucleophilic displacement between 6-chloropurine and various diamines. Phthalonitrile (PN) resin is a typical class of HPP. To verify the feasibility of DAAMP for HPP design, two new phthalonitrile monomers based on two different diamine namely DAAMP-PN were synthesized. The chemical structures of synthesized monomers were confirmed by Fourier Transform Infrared spectroscopy (FTIR) and Nuclear Magnetic Resonance (NMR). The two new DAAMP-PNs based on different diamines showed an obvious difference in thermal polymerization behavior. Multiple hydrogen bonding was exhibited in DAAMP-PN system. And the prepared DAAMP-PN polymer showed high glass transition temperature, excellent thermal and thermo-oxidative stabilities. The results demonstrated that DAAMP is a promising building-block for HPP design with flexible molecular tailorability. Highlights : A novel partial bio-based diamine-adenine-monomer platform (DAAMP) for high performance polymer (HPP) was designed. The phthalonitrile resin derived from DAAMP (DAAMP-PN) exhibited excellent thermal and thermo-oxidative stabilities. The DAAMP-PN also showed great potential in the field of functional materials.